Effect of Mineralocorticoid Receptor Antagonists on Cardiac Structure and Function in Patients With Diastolic Dysfunction and Heart Failure With Preserved Ejection Fraction: A Meta‐Analysis and Systematic Review. Issue 10 (October 2015) - Pandey, Ambarish; Garg, Sushil; Matulevicius, Susan A.; Shah, Amil M.; Garg, Jalaj; Drazner, Mark H.; Amin, Alpesh; Berry, Jarett D.; Marwick, Thomas H.; Marso, Steven P.; de Lemos, James A.; Kumbhani, Dharam J.
Abstract : Background: There has been an increasing interest in use of mineralocorticoid receptor antagonists (MRAs) in patients with heart failure with preserved ejection fraction (HFPEF). However, a comprehensive evaluation of MRA effects on left ventricular (LV) structure and function in these patients is lacking. In this meta‐analysis, we evaluated the effects of MRAs on LV structure and function among patients with diastolic dysfunction or HFPEF. Methods & Results: Randomized, controlled clinical trials evaluating the efficacy of MRAs in patients with diastolic dysfunction or HFPEF were included. The primary outcome was change in E/e', a specific measure of diastolic function. Secondary outcomes included changes in other measures of diastolic function, LV structure, surrogate markers for myocardial fibrosis (carboxy‐terminal peptide of procollagen type I [PICP] and amino‐terminal peptide of pro‐collagen type‐II [PIIINP]), blood pressure, and exercise tolerance. In the pooled analysis, MRA use was associated with significant reduction in E/e' (weighted mean difference [WMD] [95% confidence interval CI]: −1.68 [−2.03 to −1.33]; P <0.0001) and deceleration time (WMD [95% CI]: −12.0 ms [−23.3 to −0.7]; P =0.04) as compared with control, suggesting and improvement in diastolic function. Furthermore, blood pressure and levels of PIIINP and PICP were also significantly reduced with MRA therapy with no significant change in LV mass or dimensions. Conclusion: MRA therapy in patients with asymptomatic diastolic dysfunction or HFPEF is associated with significant improvement in diastolic function and markers of cardiac fibrosis without a significant change in LV mass or dimensions.